ANALISIS STRATEGI MULTISTAKEHOLDER PENGEMBANGAN DESA WISATA RAMMANG-RAMMANG - Bimantara, Teguh; A. Samsu, Andi Khairil (Program Studi Kehutanan Universitas Muslim Maros, 2024)
Tourism is currently still a priority sector for the government because it is considered capable of being a locomotive for the nation's economic movement. In Indonesia, tourist attractions have been integrated with the concept of ecotourism, namely tourism without destroying the environment so that it is sustainable. Activities that can be carried out apart from traveling are research, education and environmental services. South Sulawesi has the Rammang Rammang Tourism Village as a locus for ecotourism, namely tourism that prioritizes ecological principles. Even though the concepts offered are increasingly complex, tourists are decreasing, this is of course due to the impact of government policies during the Covid-19 pandemic until the New Normal era. Therefore, it seems necessary to develop a strategy for developing a tourist village model with a multi-stakeholder role in order to increase tourist attraction. The aim of this research is to identify management conditions, policies and develop a tourism village development strategy. The methods used are interviews, observation, questionnaires and literature review. The data obtained was then analyzed using SWOT, EFAS and IFAS. Research shows that the impact of the pandemic policy until the New Normal era has had an impact on government circles, namely a lack of contribution (Original Regional Income), for tourism managers also reduced income, and tourists are not free to explore tourist attractions. So to answer this problem a strategy model is offered, namely maximizing pentahelix involvement, planning and designing tourism innovation products, identifying market demand and building marketing strategies, as well as identifying tourism sustainability (Monitoring and Evaluation).